How do we harness adolescent values in designing health behaviour change interventions? A qualitative study. Issue 4 (4th May 2021) - Strömmer, Sofia; Shaw, Sarah; Jenner, Sarah; Vogel, Christina; Lawrence, Wendy; Woods‐Townsend, Kathryn; Farrell, David; Inskip, Hazel; Baird, Janis; Morrison, Leanne; Barker, Mary
Abstract : Objectives: Adolescent health behaviours do not support optimal development. Adolescents are reportedly difficult to engage in health behaviour improvement initiatives. Little is known about what adolescents value in relation to diet and physical activity or how best to target these in health interventions. This study explored adolescents' values in relation to diet and physical activity and how these values can inform health intervention design. Design: Qualitative semi‐structured interviews explored adolescents' lives, what they thought about diet and physical activity and what might support them to improve their health behaviours. Methods: A total of 13 group interviews were conducted with 54 adolescents aged 13–14 years, of whom 49% were girls and 95% identified as White British. Participants were recruited from a non‐selective secondary school in a large southern UK city. Inductive thematic analysis was used to identify key adolescent values. Results: Adolescents valued being with their friends, doing what they enjoyed and were good at; being healthy was important to them but only if achievable without compromising other things that are important to them. The need to be healthy was not aligned with adolescents' basic psychological needs, nor their strongly held priorities and values. Conclusions: Health is not a motivating factor for adolescents; therefore, interventions designed solely to improve health are unlikely to engage them. Instead, interventions that align with the values and priorities specified by adolescents are more likely to be effective in supporting them to eat well and be more active.